Resistance of genetically modified potatoes to Potato virus Y under field conditions - Dusi, Andre Nepomuceno; Oliveira, Cristiane Lopes de; Melo, Paulo Eduardo de; Torres, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the resistance of genetically modified clones of potato to Potato virus Y (PVY) under field conditions. Genetically modified plants were compared with nontransformed plants of the same cultivar. The plots were flanked with potato plants infected with both PVYO and PVYN strains (spread lines), in order to provide the experimental area with the source of virus, which was naturally spread by the native aphid population. The experiment was weekly monitored by visual inspections and by DAS-Elisa in the plants produced from the harvested tubers, in order to evaluate the resistance of transgenic plants throughout the plant growth cycle. By the end of the third year, no infection symptoms were observed in the 1P clone; clone 63P showed 1% of infection, in contrast to about 90% of nontransformed plants infected. The stable expression of resistance to PVY provided by the coat protein gene was obtained in genetically modified clones of potato plants cultivar Achat under field conditions, during three consecutive years.